Effect of different heat setting temperatures on the properties of dyed and undyed knitted polyester fabrics / Najihah Esa - Esa, Najihah (Faculty of Applied Sciences, 2018)
The aim of this study is to analyse the effects of different heat setting temperatures on the properties of dyed and undyed knitted polyester fabrics. Specifically, the physical properties of the fabrics were evaluated in terms of fibre count, mass per unit area, wales and courses per inch and also fabric thickness. Meanwhile, the mechanical properties evaluated was the bursting strength of the fabrics. Two polyester fabric samples were selected one of which was dyed and the other one undyed. Subsequently, heat-setting process was conducted using three temperatures which were 160˚C, 170˚C and 180˚C at a constant dwell time of 5 minutes followed by the analysis and gathering of data. The results from the heat-setting treatment done showed that the physical and mechanical properties of both dyed and undyed knitted polyester fabrics are mostly not affected by the different heat-setting temperatures used. However, there was a significant improvement in the colour fastness properties of the dyed fabrics and no yellowing effect was observed on the undyed fabrics. This paper can be improved by selecting fabric samples that have not undergone any kind of treatment in the industry so that the results are more consistent and reliable. The handling of fabric samples can also be improved as it may negatively affect the results. Future researchers can obtain raw fabric samples directly from a manufacturing factory before the samples are subjected to any kind of treatment.